Oral-diadochokinesis rates for Spanish, German and Czech: reference values for normotypical adults - Camargo-Mendoza, Maryluz; Nöth, Elmar; Mekyska, Jiri; Orozco-Arroyave, Juan Rafael (Revista de Investigación en Logopedia, 2023)
Oral diadochokinesis (oral-DDK) is one of the common maximum performance task used in clinical practice to evaluate the oral motor mechanism.  Although there are reference values ​​for some languages, there are no recent publications of adult population speaking Spanish, German or Czech.Aims: 1) to describe the values ​​of oral-DDK in adult speakers of Spanish, German and Czech, 2) to determine the influence of gender on the values ​​of oral-DDK, 3) to determine the influence of age on the values ​​of oral-DDK and, 4) to compare the inter-language values ​​of the oral-DDK.Methods & Procedures: the recordings of 189 healthy adults were considered (between 26 to 86 years), 94 females and 95 males, while producing the sequential motion rate (SMR) /pa-ta-ka/. Count-by-time method was used using an acoustic analysis software. Oral-DDK averages were established for each language and the effect of gender and age was determined. The variability of the measure among languages ​​was also established.Results: reference data were obtained for each language. Age did not show any significant effect on oral-DDK despite its decline as age advanced; there was no gender effect on the oral-DDK, and the comparison of the oral-DDK among languages showed statistically significant differences.Conclusions: This study determined the reference data of the oral-DDK for Spanish, German and Czech and found significant differences among the three languages ​​and no significant effects of age or gender on the measure studied.
Keywords: Oral-diadochokinesis; normative data; adults; Spanish; German; Czech